A Complete Overview On Primula Vulgaris: Pharmaceutical sciences- Pharmacy - Talreja, Shreya; Tiwari, Dr Shashank (International Journal of Life Science and Pharma Research, 2023)
Primula vulgaris, also known as the common or English primrose, is a perennial herbaceous plant renowned for itsdelicate and vibrant flowers. Embedded in various traditions, this charming species holds cultural significance associated with spring,love, and healing. Throughout history, it has been utilized in traditional medicine for its potential medicinal properties, includinganti-inflammatory effects, skin health benefits, and hormonal balance support. Recent scientific research has delved into exploringthe phytochemical composition of primrose and its therapeutic potential. Studies have revealed the presence of compounds likesaponins, flavonoids, phenolic acids, and essential fatty acids, which contribute to its reported medicinal effects. However, theapplications of primrose extend beyond medicine; it also finds use in culinary and cosmetic practices. The flowers serve as ediblegarnishes in salads, desserts, and beverages, while primrose oil extracted from the seeds is valued in the cosmetic industry for skincare and hair care applications. In addition to its various uses, botanical science research has focused on primrose's geneticdiversity, ecological significance, and potential roles in climate change adaptation. Consequently, conservation efforts are underwayto protect its natural habitats and preserve its biodiversity. This paper aims to provide a comprehensive overview of Primulavulgaris, covering its cultural, medicinal, culinary, and ecological aspects. By examining its historical significance, traditional uses inmedicine, and scientific evidence supporting its potential benefits, the paper seeks to emphasize the enduring symbolism ofprimrose, a testament to beauty, tradition, and the intricate relationship between humanity and the natural world. As ongoingresearch unveils its hidden potential, primrose remains a fascinating subject for scientific exploration and cultural appreciation.